Post craniotomy and electrocardiographic monitoring - Lesmana, Hendy; Pujianto, Ahmat; Purnomo, Bayu (International Journal of Research in Medical Sciences, 2021)
Background: Post craniotomy management mainly emphasizes monitoring complications that occur. Close supervision and monitoring are needed in post craniotomy patients, especially in the first 48 hours so that the patient is placed in the intensive care unit (ICU). Various studies have identified various complications that arise from mild complications to severe complications, namely the death of patients after craniotomy, so that hemodynamic monitoring tool are needed. Electrocardiography is one of the hemodynamic monitoring tools in the intensive care room which is very useful in monitoring heart rhythm abnormalities in post-craniotomy patients. Methods: This descriptive study was conducted on 30 respondents post craniotomy and were treated in the Intensive Care Unit (ICU) for 1-3 days of treatment. An electrocardiographic monitoring analysis was performed on 30 respondents, then confirmed by examination of blood electrolytes and blood gas analysis. Results: In this study 90% of respondents experienced electrocardiographic rhythm abnormalities, 50% sinus arrhythmia, 33.3% sinus tachycardia, 6.7% sinus bardycardia. The results of electrolyte examination 18 respondents experienced electrolyte balance disorders where 4 respondents experienced hyponatremia, 7 respondents experienced hypernatremia+hyperchloremia, 1 respondent experienced hyponatremia+hypochloremia, 5 respondents experienced hyperchloremia and 1 respondent experienced hypokalemia. There are 7 respondents experiencing acid-base balance disorders. Conclusions: in this study showed that most of the patients after craniotomy had heart rhythm abnormalities. The most common arrhythmia is sinus arrhythmia. The pathological conditions that accompany these rhythm disturbances are mostly caused by electrolyte balance disorders, acid-base balance disorders or a combination of the two disorders.